2017
DOI: 10.26719/2017.23.8.551
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge and habits of adolescents aged 9 to 13 years in Sharjah, United Arab Emirates: a crosssectional study

Abstract: Connaissances nutritionnelles et habitudes alimentaires chez les adolescents aux Émirats arabes unis : étude transversaleRÉSUMÉ De bonnes connaissances nutritionnelles ainsi que des comportements alimentaires sains sont importants pour les adolescents afin d'éviter les problèmes de santé persistants à l'âge adulte. La présente étude transversale avait pour objectif de fournir des données de base sur les connaissances nutritionnelles et les habitudes alimentaires chez les adolescents à Sharjah. Des données ont … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
3
14
0
1
Order By: Relevance
“…The current study revealed that, a positive correlation between the studied subjects knowledge, nutritional habit and general appearance with no statistically significant difference. These findings were in agreement with Al-Yateem and Rossiter (2017) reported that a positive association between higher levels of nutritional knowledge and healthier eating habits, including eating more fruit and vegetables, eating more regularly at breakfast and consuming less unhealthy snacks and less fast food.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study revealed that, a positive correlation between the studied subjects knowledge, nutritional habit and general appearance with no statistically significant difference. These findings were in agreement with Al-Yateem and Rossiter (2017) reported that a positive association between higher levels of nutritional knowledge and healthier eating habits, including eating more fruit and vegetables, eating more regularly at breakfast and consuming less unhealthy snacks and less fast food.…”
Section: Discussionsupporting
confidence: 93%
“…This finding coincides with Nichols, Francis, and Dalrymple (2014) conducted a study in Trinidad and Tobago, found that a low level of dietary knowledge among primary school children. In the same stream Al-Yateem and Rossiter (2017) who evaluated the nutritional knowledge and habits of adolescents aged 9 to 13 in Sharjah, United Arab Emirates and reported that most students (86%) had poor nutritional knowledge, especially in key areas: what are healthy snacks and foods, daily dietary requirements and food components (for example, fiber, fat, and sugar).…”
Section: Discussionmentioning
confidence: 99%
“…As this eliminates filling in the correct answer by chance, this might have influenced the lower knowledge score. However, another cross-sectional study reported that 86% of the participating United Arab Emirati adolescents had a low level of dietary knowledge [ 28 ]. With regard to the parents, their average dietary knowledge score was 63%, thus scoring higher than their children.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the respondents have poor knowledge towards reducing malnutrition 451 (80.2%) which is contrary to studies elsewhere in Southwest Ethiopia, Nairobi city, Kenya, Palestine, and Darab city, Fars province, Iran where 201 (44.2%), 32.7%, 52.4%, and 38.5% of the respondents had poor knowledge, respectively [ 26 , 41 , 42 ]. Findings from studies conducted in Sharjah, United Arab Emirates reveals that 86% of adolescents had poor knowledge of nutrition [ 43 ]. Results in this study reported that breakfast is the most important meal of the day 89.9%, this is in line with studies conducted in China who reported 68.8% and South Africa who reported 87.6% [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%